Nociceptor-localized KCC2 suppresses brachial plexus avulsion-induced neuropathic pain and related central sensitization - Hang Xian; Huan Guo; Yuan-Ying Liu; Sui-Bin Ma; Rui Zhao; Jian-Lei Zhang; Hang Zhang; Rou-Gang Xie; Xu-Cheng Guo; Jie Ren; Sheng-Xi Wu; Ceng Luo; et al. (Cell & Bioscience)
Abstract Lack in understanding of the mechanism on brachial plexus avulsion (BPA)-induced neuropathic pain (NP) is the key factor restricting its treatment. In the current investigation, we focused on the nociceptor-localized K+-Cl− cotransporter 2 (KCC2) to investigate its role in BPA-induced NP and related pain sensitization. A novel mice model of BPA on the middle trunk (C7) was established, and BPA mice showed a significant reduction in mechanical withdrawal threshold of the affected fore- and hind- paws without affecting the motor function through CatWalk Gait analysis. Decreased expression of KCC2 in dorsal root ganglion (DRG) was detected through Western blot and FISH technology after BPA. Overexpression of KCC2 in DRG could reverse the hyperexcitability of DRG neurons and alleviate the pain of BPA mice synchronously. Meanwhile, the calcium response signal of the affected SDH could be significantly reduced through above method using spinal cord fiber photometry. The synthesis and release of brain-derived neurotrophic factor (BDNF) was also proved reduction through overexpression of KCC2 in DRG, which indicates BDNF can also act as the downstream role in this pain state. As in human-derived tissues, we found decreased expression of KCC2 and increased expression of BDNF and TrκB in avulsed roots of BPA patients compared with normal human DRGs. Our results indicate that nociceptor-localized KCC2 can suppress BPA-induced NP, and peripheral sensitization can be regulated to reverse central sensitization by targeting KCC2 in DRG at the peripheral level through BDNF signaling. The consistent results in both humanity and rodents endow great potential to future transformation of clinical practice.